Teachers’ Reflection on Meditation Practice in Basic-Level Classroom Instruction - Hari Acharya, Nara; Ram Pokhrel, Tika (Education and Development, 2026)
This study explored the teachers’ reflections on the meditation strategies used during the training sessions for teaching and learning mathematics. The meditation practice was conducted among 88 basic-level teachers who participated in the physical or the online mode of training in the teachers' professional development (TPD) training program organized by government of Nepal. All the participants were asked to write their reflections by incorporating the learning and perceptions of meditation stories presented during teaching and learning mathematics. Four of the participants from each cohort, out of all participants, were asked to express their feelings on the meditation strategy on the basis of the process, content, and method of delivery of the content and recorded them. The data were then transcribed and linked with the written form of reflection. The themes were developed. The analysis of data suggests that the meditation strategy ensures focus and concentration with playful learning. It helps developing critical and creative thinking, with memory and understanding of any content through service learning and integrated learning. Participants teachers have shown commitment in applying meditation strategies their classroom instruction.